Pengaruh Variasi Produk, Harga, Kualitas Pelayanan dan Kepercayaan terhadap Loyalitas Pelanggan Koperasi Serba Usaha Ngebrak Store - Ma’ruf Amri; Bahtiar Efendi; Muhamad Asif Maulana Akbar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to determine the effect of product variety, price, service quality, and trust on customer loyalty at the Ngebrak Store Multipurpose Cooperative (KSU) in the Pondok Pesantren Tahfidzul Qur’an Baitul Abidin Darussalam, Kalibeber, Mojotengah District, Wonosobo Regency. This research employs a quantitative approach, using multiple linear regression analysis for data analysis. The sampling method applied is non-probability sampling with purposive sampling technique. The sample size was determined using the Hair formula, which resulted in 126 respondents who are customers of the Ngebrak Store Multipurpose Cooperative. The findings of this study are as follows: (1) Product variety has no positive effect on customer loyalty, with a t-value (0.141) < t-table (1.980), a significance level of (0.888), and a regression coefficient of 0.007. (2) Price has a positive effect on customer loyalty, with a t-value (2.680) > t-table (1.980), a significance level of (0.008), and a regression coefficient of 0.202. (3) Service quality has a positive effect on customer loyalty, with a t-value (1.594) > t-table (1.980), a significance level of (0.001), and a regression coefficient of 0.276. (4) Trust has no positive effect on customer loyalty, with a t-value (3.278) > t-table (1.980), a significance level of (0.114), and a regression coefficient of 0.161.